2017
DOI: 10.1038/s41598-017-03314-7
|View full text |Cite
|
Sign up to set email alerts
|

Hatching enzymes disrupt aberrant gonadal degeneration by the autophagy/apoptosis cell fate decision

Abstract: Environmental stressors, gonadal degenerative diseases and tumour development can significantly alter the oocyte physiology, and species fertility and fitness. To expand the molecular understanding about oocyte degradation, we isolated several spliced variants of Japanese anchovy hatching enzymes (AcHEs; ovastacin homologue) 1 and 2, and analysed their potential in oocyte sustenance. Particularly, AcHE1b, an ovary-specific, steroid-regulated, methylation-dependent, stress-responsive isoform, was neofunctionali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…qPCR analysis of each cell population depicted a substantially elevated CaM level in D population than G-cell fraction, while PMCA1b transcription was further suppressed in LC3-positive germ cells (Figure 4G). Our data suggest that cellular-level calcium ion threshold is critical for cell survivability (Borodkina et al., 2016, Chakraborty et al., 2017). Longer incubation with BAPTA_AM, and not with EGTA, increased the ERβ2-KD-XX gonad size and germ cell numbers, further emphasizing that intracellular Ca 2+ overload is crucial for increased PGC degeneration and further germ cell loss (Figures 4H–4J).…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…qPCR analysis of each cell population depicted a substantially elevated CaM level in D population than G-cell fraction, while PMCA1b transcription was further suppressed in LC3-positive germ cells (Figure 4G). Our data suggest that cellular-level calcium ion threshold is critical for cell survivability (Borodkina et al., 2016, Chakraborty et al., 2017). Longer incubation with BAPTA_AM, and not with EGTA, increased the ERβ2-KD-XX gonad size and germ cell numbers, further emphasizing that intracellular Ca 2+ overload is crucial for increased PGC degeneration and further germ cell loss (Figures 4H–4J).…”
Section: Resultsmentioning
confidence: 78%
“…Interestingly, the total OLVAS expressions remained unaffected at stages 22 and 33 of ERβ2-KD-XX embryos and significant suppression was noticed at 4 daf, at which point the mislocalized cells became autophagic (Figure 3G). This autophagy induction might be associated with the disturbance in E 2 /ER associated ion homeostasis (Chakraborty et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it was reported that estrogens could increase the ovarian weight [37] and stimulate the proliferation of granulosa cells [38], while the ovarian androgens acting as apoptotic factors could cause deterioration of ovarian follicles by increasing the number of pyknotic granulosa cells and degenerated oocytes and then result in the decreasing ovarian weight [39,40]. An increased androgen to estrogen ratio was also found in follicular fluid of atretic follicles [41].…”
Section: Discussionmentioning
confidence: 99%
“…Our results from the promoter assay confirmed that an active promoter is maintained after retrocopy, and strongly supported the above hypothesis. In recent years, a report was published describing that anchovies, which are related to herring and have intron-containing HEs , express some splicing variants of HEs in the ovary 40 . Although there is no detailed mention of TSS in this report, this implies that the HE containing promoter encompasses the potential to express in the ovary.…”
Section: Discussionmentioning
confidence: 99%